Unintentional strangulation by a cervical collar after attempted suicide by hanging. Issue 6 (23rd December 2010) - Lemyze, Malcolm; Palud, Aurore; Favory, Raphael; Mathieu, Daniel
Abstract : We report the case of a young man who attempted suicide by hanging and whose neurological status deteriorated until the cervical collar, that had been correctly placed by the prehospital team, was removed. We discuss the physiopathological mechanisms leading to death in hanging that is, a blockage of the blood stream to the brain leading to vasogenic and cytotoxic cerebral edema rather than asphyxia or spinal fracture. Our case supports the early removal of neck stabilization devices that can dangerously harm the patient after an attempted suicide by hanging, by increasing intracerebral pressure.